Rancang Bangun Smart System Safety Doorlock pada Kamar Crew Kapal Menggunakan Face Recognition dengan Esp32 Wrover Cam - Pande Gede Agus Parsana Yudha; Edi Kurniawan; Dyah Ratnaningsih (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2024)
Security systems in the maritime sector are crucial for preventing criminal activities and theft on board ships. The physical key systems commonly used today have vulnerabilities that can be exploited by unauthorized individuals. This research aims to design and test a smart door lock system using facial recognition with the ESP32 Wrover cam and a 4x4 Keypad as an additional security measure. The test results show that the system successfully recognizes faces with a 90% success rate at a distance of 15-100 cm, although there is a decrease in efficiency when more than one face is registered. The system also demonstrated 100% success in